2021
DOI: 10.3389/fpsyg.2021.621418
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Influencing Factors of Cyberbullying Among Chinese College Students Incorporated With Digital Citizenship: From the Perspective of Individual Students

Abstract: Understanding the influencing factors of cyberbullying is key to effectively curbing cyberbullying. Among the various factors, this study focused on the personal level of individual students and categorized the influencing factors of cyberbullying among college students into five sublevels, i.e., background, Internet use and social network habits, personality, emotion, and literacy related to digital citizenship. Then a questionnaire survey was applied to 947 Chinese college students. The results show that cyb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 65 publications
0
22
0
5
Order By: Relevance
“…Following the review of previous research [ 12 , 15 ] and consultation with researchers and health professionals, a short, self-administered questionnaire was designed to investigate the ecological system information. Before the formal investigation, 2 experts in pedagogy and health education were invited to inspect the rationality and logic of the questionnaire and asked to modify any unclear expressions.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Following the review of previous research [ 12 , 15 ] and consultation with researchers and health professionals, a short, self-administered questionnaire was designed to investigate the ecological system information. Before the formal investigation, 2 experts in pedagogy and health education were invited to inspect the rationality and logic of the questionnaire and asked to modify any unclear expressions.…”
Section: Methodsmentioning
confidence: 99%
“…In contrast to the abundance of large-scale studies on colleges, high schools, and junior and elementary schools, there have been relatively few attempts to collect data among vocational high schools. [ 10 , 12 ] Understanding CB and CV among this group is an important part of public health, and the present study attempts to help fill this gap.…”
Section: Introductionmentioning
confidence: 99%
“…However, other researchers claimed a possible negative association between perceived anonymity and cyberbullying behavior in China. Students in China have to attend some lessons on Internet literacy, which indicates that they may identify themselves with their role as digital citizens in the anonymous online world, which may be negatively correlated with the degree of cyberbullying behavior [ 15 ]. Moreover, China is a country that the network real-name system has been largely achieved, which could change the nature of the phenomenon.…”
Section: Introductionmentioning
confidence: 99%
“…The study recommends enhancing digital citizenship education to prepare the learners for the appropriate, responsible, and ethical use of technology. Zhong et al (2021) The results of this study have shown that there is a low level of cyberbullying among Chinese students at colleges. The study also indicates that factors such as gender have a significant impact on cyberbullying.…”
Section: Integration Of Digital Citizenship and Educationmentioning
confidence: 71%
“…On the other hand, a study in the USA stated that schools and universities have underlined the negative features of technology and how it is misused by users (Walters et al, 2019). Similarly, Zhong et al (2021) stated that understanding the influencing factors of technology is key for the effective reduction of cyberbullying. According to this study, these influencing factors include the individual level of learners and have classified cyberbullying between learners in the college into five sublevels.…”
Section: Integration Of Digital Citizenship and Educationmentioning
confidence: 99%